Effect of Etching on the Optical, Morphological Properties of Ag Thin Films for SERS Active Substrates - Desapogu Rajesh; M. Mahendar; C. S. Sunandana (Journal of Chemistry)
Structural, optical, and morphological properties of Ag thin films before and after etching were investigated by using X-ray diffraction, UV-Vis spectrophotometer, and field emission scanning electron microscopy (FESEM). The HNO3 roughened Ag thin films exhibit excellent enhancement features and better stability than pure Ag thin films. Further, the Ag nanostructures are covered with Rhodamine 6G (Rh6G) and then tested with surface enhanced raman spectroscopy (SERS) for active substrates. Etched Ag films were found to exhibit a strong SERS effect and excellent thermal stability. Hence, the present method is found to be useful in the development of plasmon-based analytical devices, especially SERS-based biosensors.